Analisis Kemampuan Numerik Siswa Kelas V dalam Mengerjakan Soal Tipe HOTS - NurBerlianty Silalahi; Deri Hendriawan (Universitas Muhammadiyah Kuningan, 2022)
Numeric capability is a person's capability to formulate, define, and interpret Mathematics in various contexts. This ability is also included in a person's high-level reasoning ability and ability in a problem that is related to digits.This study aims to identify the numeric capabilities of fifth-grade students by carrying out a trial test with numeric questions of the higher order of thinking skill(HOTS) type.The type of research used is qualitative with content analysis method accomplished at Lialang State Elementary School.The research respondent were fifth-grade students consisting of 35 students. The data collection technique was carried out with the interviews, observations, and trial test. The results of the study show that the numerical ability of students has a percentage of 53.33% of the students were in the medium-ability group, and 46,67% of the students were in the low-ability group.